Impact of Assistive Technologies in Academic Evaluation for Students with Specific Learning Disabilities Studying in Secondary Schools of Koshikode District, Kerala - Bibi C.B; V. Mrunalini (International Journal of Children, 2026)
The inclusion of assistive technologies (AT) in academic assessment has made the learning experience of students who have specific learning disabilities (SLDs) much more fruitful. This paper discusses the effects of text-to-speech (TTS) and speech-to-text (STT) as applied in the academic performance of secondary school students with SLDs in Kerala regarding their effectiveness in improving their examination performance, understanding, and confidence. This method was a mixed design, which required 30 special educators to be involved in the study by completing a structured questionnaire and providing direct observations of 15 students taking exams assisted using assistive technology and in the absence of it. The results show that TTS and STT technologies used by students led to better understanding of the material, lower levels of anxiety during examination, and better writing than the traditional way of evaluation. Text-to-speech was useful to students with reading problems to interpret the questions on the examinations better, whereas speech-to-text allowed students with handwriting and spelling problems to make their knowledge clear. On the whole, these technologies contributed to the improvement of processing information, responding correctly and feeling more confident during exams in students. Teachers also noted a high degree of independence, participation and less stress amongst students who use assistive technology. Within the study, it is identified that a good policy support, teacher training, and more accessible assistive technologies are needed. The barriers can be addressed to facilitate the highly inclusive, accessible, and very equitable academic evaluation system among students with SLDs
Keywords: Academic evaluation; Text-to-Speech; assistive technology; specific learning disabilities; speech-to-text